Explaining differences in women's working time in European cities. Issue 2 (15th March 2017) - Jensen, Per H.; Møberg, Rasmus Juul; Och, Ralf; Pfau-Effinger, Birgit
ABSTRACT: Women's work-time pattern in Europe is highly heterogeneous; some women work short or long part-time hours, while others work full-time. Few studies, however, have analysed the factors constituting women's work-time pattern. The article aims to explain why women's working time differs in five relatively big European cities, which represent an urban environment that is particularly supportive to women's employment, and the study is based on a new original telephone survey from 2013 among women 25–64 years of age. It is hypothesized and analysed how women's work-time pattern is the result of women's family-cultural orientation, individual and family characteristic, the gendered division of household task, women's position in the vertical and horizontal division of labour, and city of residence. Findings support the theoretical assumptions that there is a significant relationship between family-cultural orientation and work practices.